IMPLEMENTASI KEBIJAKAN PROGRAM KAMPUNG KELUARGA BERENCANA - KAMPUNG BAIMAN (KKB-KB) DI KOTA BANJARMASIN - normajatun normajatun; Sitna Hajar Malawat; Fika Fibriyanita (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2018)
Developing countries are always experiencing the main problem of development, where one of the points of development problems concerning the problem of a large population with a low quality of life Banjarmasin city government has a policy. namely Kampung Keluarga Berencana - Kampung Baiman (KKB-KB). The KKB-KB program not only prioritizes family planning programs but all sectors, such as health development, population administration and residential development. The KKB-KB program is expected to improve the quality of life of the community. This study uses a qualitative approach to collect data and analyze data then interpreted.